CV. Tirta Buana Global Expansion in Construction Consultancy - Indras Ghosh; Khusni Mubarrok; Liem Gai Sin; Alka Maurya (LPPM of NAROTAMA UNIVERSITY, 2018)
This paper examines the different organisation aspect of a construction consultancy firm in Surabaya, Indonesia to find a suitable way for the firm to expand its operation across international borders. The purpose of this paper is to develop a sound research model to help understand the working of the different organisation and operation changes for a domestic firm to be able to expand globally. Qualitative data collected through physical observation and interviews. Additional secondary data was obtained through reports, articles, and journals